STUDY OF CATECHIN CONCENTRATION FROM GAMBIER AND GREEN TEA ON THE EFFECT OF SUPPRESSING THE PROGRESS OF GROWTH OF Pseudomonas sp BACTERIA IN TILAPIA (Oreochromis niloticus) - Ronald Sohahau Manao; Reni Desmiarti; Suparno (PT Inovasi Pratama Internasional, 2026)
Gambir and green tea hold functional compounds contained in the category of polyphenolic compounds, one component of which is catechins. Catechins have antimicrobial properties because they have the ability to break down microbial cell chambers or precipitate proteins. The microbe Pseudomanas sp is often found in tilapia with a high level of pathogenicity. This research aims to examine the effect of Gambir Catechin and Green Tea concentrations to suppress the growth of Pseudomonas sp tilapia bacteria. The research method applied is tabulation and descriptive method. The concentration of catechin compounds was modified by 4%, 6%, 8%, and 10%. The results showed that the antimicrobial effect developed with an increase in the concentration of catechin compounds for catechin from gambier and green tea. This shows that there is a strong positive relationship between concentration and zone of inhibition and the catechin compounds of gambier and green tea have antimicrobial effects against Pseudomonas sp. The results of this research can be applied to develop tilapia aquaculture in the future.